Study of the GPS inter-frequency calibration of timing receivers. (12th December 2017) - Defraigne, P; Huang, W; Bertrand, B; Rovera, D
Abstract: When calibrating Global Positioning System (GPS) stations dedicated to timing, the hardware delays of P 1 and P 2, the P ( Y )-codes on frequencies L 1 and L 2, are determined separately. In the international atomic time (TAI) network the GPS stations of the time laboratories are calibrated relatively against reference stations. This paper aims at determining the consistency between the P 1 and P 2 hardware delays (called d P 1 and d P 2) of these reference stations, and to look at the stability of the inter-signal hardware delays d P 1–d P 2 of all the stations in the network. The method consists of determining the d P 1–d P 2 directly from the GPS pseudorange measurements corrected for the frequency-dependent antenna phase center and the frequency-dependent ionosphere corrections, and then to compare these computed d P 1–d P 2 to the calibrated values. Our results show that the differences between the computed and calibrated d P 1–d P 2 are well inside the expected combined uncertainty of the two quantities. Furthermore, the consistency between the calibrated time transfer solution obtained from either single-frequency P 1 or dual-frequency P 3 for reference laboratories is shown to be about 1.0 ns, well inside the 2.1 ns uB uncertainty of a time transfer link based on GPS P 3 or Precise Point Positioning. This demonstrates the good consistency between the P 1 and P 2 hardware delays of the reference stations used for calibration in the TAI network. The long-term stability of the inter-signal hardware delays is also analysed from the computed d P 1–d P 2. It is shown that only variations larger than 2 ns can be detected for a particular station, while variations of 200 ps can be detected when differentiating the results between two stations. Finally, we also show that in the differential calibration process as used in the TAI network, using the same antenna phase center or using different positions for L 1 and L 2 signals gives maximum differences of 200 ps on the hardware delays of the separate codes P 1 and P 2; however, the final impact on the P 3 combination is less than 10 ps.